Measurements of Stratospheric Water Vapor at Mauna Loa and the Effect of the Hunga Tonga Eruption. Issue 8 (25th April 2023) - Nedoluha, Gerald E.; Gomez, R. Michael; Boyd, Ian; Neal, Helen; Allen, Douglas R.; Lambert, Alyn; Livesey, Nathaniel J.
Abstract: The eruption of Hunga Tonga in January 2022 injected an amount of water vapor into the stratosphere that is unprecedented in the satellite era. In the ensuing months Aura Microwave Limb Sounder measurements showed that this plume of water vapor spread from its original injection site at 20.5°S to Mauna Loa, Hawaii at 19.5°N, where an increase was observed in April by the ground‐based Water Vapor Millimeter‐wave Spectrometer instruments. Interannual variations in water vapor occur over Mauna Loa due to both dynamical variations in the tropical stratosphere and variations in the amount of water vapor crossing the tropical tropopause, and we place the observed stratospheric water vapor increase from Hunga Tonga into context of these other variations that have been observed since 2013. Plain Language Summary: The eruption of the undersea Hunga Tonga volcano on 15 January 2022 injected large amounts of water vapor into the stratosphere, breaking all records for direct injection of water vapor in the satellite era. During the ensuing months this plume of water vapor spread from the original injection site at 20°S to cover much of the Southern Hemisphere and reached as far as 20°N, where it was first observed by a ground‐based microwave instrument at Mauna Loa, Hawaii in April 2022. These ground‐based measurements capable of detecting water vapor at the altitude of the plume have been made since 2013, and we compare the sudden increase in water vapor caused by the arrival of this plume over Mauna Loa with other variations that have occurred over the last decade. This study lays the ground‐work for an understanding of the effect of the water vapor injected by the eruption on overall water vapor in the stratosphere in the coming years. Key Points: Aura MLS measurements showed that water vapor from the Hunga Tonga eruption spread to 20°N in April 2022 Ground‐based instruments at Mauna Loa observed an increase in the lower stratosphere in April 2022 The April 2022 increase in water vapor in the upper stratosphere over Mauna Loa is placed in context of interannual variations since 2013